Getting it Wrong : How Canadians Forgot Their Past and Imperilled Confederation - Romney, Paul, 1945- (Book collections on Project MUSE., 1999)
This provocative book explains how divergent views of Canada's past have sown dissension between Quebecois and other Canadians, disclosing a lost middle ground between the Canadian nationalist and Quebec nationalist visions of Canadian history.